The Implications of Empathy in Our Contexts - Pedraza Hernández, Blanca Ximena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Being a teacher entails having to be dynamic and active when facing all of the different challenges that our field demands of us. In this case, English is not an exception to this fact. In order to teach the language, we must undergo a constant reflective process where we make use of our creativity and eclectic view of pedagogy as a means of exploring and understanding our students’ particularities. By doing so, we can get to know their backgrounds to foster their learning process.